Capital structure and corporate performance of Malaysian construction sector - Ong, Tze San; Teh, Boon Heng (Center for Promoting Ideas (CPI), USA, 2011)
This paper investigates the relationship of capital structure and corporate performance of firm before and during crisis (2007). This study focuses on construction com panies which are listed in Main Board of Bursa Malaysia from 2005 to 2008. All the 49 construction companies are divided into big, medium and small sizes,based on the paid - up capital. The result shows that there is relationship between capital structure a nd corporate performance and there is also evidence shows that no relationship between the variables investigated. For big companies, ROC with DEMV and EPS with LDC have a positive relationship whereas EPS with DC is negatively related. In the interim, only OM with LDCE has positive relationship in medium companies and EPS with DC has a negative relationship in small companies. In sum, the outcome reveals that the relationship exists between capital structure and corporate performance in selected proxies.